Associations with meibomian gland loss in soft and rigid contact lens wearers. Issue 1 (February 2022) - Harbiyeli, Ibrahim Inan; Bozkurt, Banu; Erdem, Elif; Ozcan, Hamide Gizem; Cam, Burcu; Sertdemir, Yasar; Yagmur, Meltem
Abstract: Purpose: This study aimed to evaluate the structural changes in meibomian glands (MGs) and meibomian gland dysfunction (MGD)-associated ocular surface alterations in contact lens (CL) wearers. Methods: This prospective, multi-center, cross-sectional study included 44 soft CL wearers, 21 rigid CL wearers, and 26 healthy non-wearers. After completing the Ocular Surface Disease Index (OSDI) questionnaire, the participants were examined for lid margin abnormalities, tear breakup times, ocular surface staining, meibum quality and expressibility. Afterwards upper and lower eyelid meibography and Schirmer I test were performed. Results: A total of 91 participants (64 females and 27 males) (91 eyes) were classified into three groups. The mean percentage of meibomian gland loss (PMGL) was 25.3 ± 12.5 % in soft CL wearers, 34 ± 13.4 % in rigid CL wearers, and 18.4 ± 9.2 % in the control group. Mean OSDI score was higher in soft CL wearers (15.5 ± 18) than in the control group (3.5 ± 2.6) (p < 0.001) and the OSDI scores were correlated with mean PMGL in CL wearers (r = 0.411, p = 0.002, r = 0.588, p = 0.005, respectively). In soft CL wearers, the duration of CL use was the only predictive variable for mean PMGL in multivariate analysis. In a regression model including both CL groups, age and rigid CL material were predictive variables for mean PMGL. Conclusions: CL use may cause MGD and this effect may be more pronounced in rigid CL wearers. In soft CL wearers, the duration of CL use is an important variable associated with MG loss, and subjective symptoms may guide the prediction of MG loss in these cases.